BXL Universel II : multipli.city. - De Naeyer, Christine; Fol, Carine; Nasielski, Tania; Salesse, Pascale; Corijn, Eric; Bergen, Véronique; Cheval, Florence; De Wit, Dirk; Joye, Sofie; Fol, Carine; Lamrabet, Rachida; Missal, Emma (Bruxelles : CFC-Éditions, 2021)
Baba-Ali, Younes ; Beeckman, Vincen ; Chaushova, Aleksandra ; Effi & Amir ; Emmerich, Hadassah ; Gbaguidi, Pélagie ; Goldrajch, Stephan ; Montiel-Soto, Sabrina ; Raimondo, Anna ; Rosell Albear, Lázara ; Tabti, Oussama
Being the most cosmopolitan city in the world after Dubai, Brussels is staunchly pluralistic. As the second chapter in a trilogy, BXL UNIVERSEL II: multipli.city brings together a diverse company of artists, authors, thinkers, players in the field and citizen associations who both question and celebrate its complexity and its rich diversity, and emphasies the unifying role of culture in this world-city.
BXL UNIVERSEL II: multiplicity, CENTRALE for contemporary art, Brussel, 25.03 > 12.09.2021
boek